Development of executive functions in late childhood and the mediating role of cooperative learning: A longitudinal study - Segundo Marcos, Rafael Ibán; Merchan Carrillo, Ana; López-Fernández, Verónica; Daza-González, María Teresa (Cognitive Development, 2023)
We examine the developmental changes in Executive functions (EFs) throughout late childhood and how the contextual factor of classroom methodology mediates such changes. Using data collected from fifty-three pupils at two time points (between the 5th and 6th grades of Primary School) we observed the longitudinal development of cool (Working Memory (WM), Cognitive Flexibility, Inhibitory Control, and Planning) and hot-EFs (Emotional Intelligence-EI-). The participants were selected from two schools with different methodological approaches (Cooperative and Individualistic learning) to examine the mediating role of classroom methodologies in developmental changes in EFs. The results revealed age-related improvements in performance on WM, cognitive flexibility, and planning tasks. Moreover, Cooperative Learning (CL) significantly affected performance on WM and self-control tasks. Our findings highlight the importance of studying the development of EFs at the end of the Primary School stage, since natural development involves numerous contextual factors that deserve attention, particularly for improving methodological proposals and learning processes.
Keywords: executive functions; development; cooperative learning; classroom methodology; JCR; Scopus